2021
DOI: 10.1097/mog.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in chronic pancreatitis: risk factors and natural history

Abstract: Purpose of review The purpose of this review is to delineate risk factors for the development of diabetes in patients with chronic pancreatitis. The natural history including progression to diabetes and complications that develop once diabetes occurs in chronic pancreatitis is also reviewed. Recent findings Studies have found that predictors of diabetes in chronic pancreatitis include both risk factors for type 2 diabetes (e.g., obesity, genetic variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
(51 reference statements)
2
17
0
1
Order By: Relevance
“…Therefore, it may be speculated that diabetes in the context of acute pancreatitis is mediated through different mechanisms compared to those involved in the development of diabetes in patients with CP. Generally, in the latter setting, PPDM is interpreted as a function of the duration of pancreatitis, as the increased risk of diabetes over time reflects accumulation of damage to the pancreatic parenchyma caused by chronic inflammation 33 . Since pancreatic calcifications are expression of an chronic inflammatory tissue injury, it is not surprising that our study identified them as an independent predictor of PPDM, which is in line with previous reports (Table 4).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, it may be speculated that diabetes in the context of acute pancreatitis is mediated through different mechanisms compared to those involved in the development of diabetes in patients with CP. Generally, in the latter setting, PPDM is interpreted as a function of the duration of pancreatitis, as the increased risk of diabetes over time reflects accumulation of damage to the pancreatic parenchyma caused by chronic inflammation 33 . Since pancreatic calcifications are expression of an chronic inflammatory tissue injury, it is not surprising that our study identified them as an independent predictor of PPDM, which is in line with previous reports (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, until recently, the extent of PPDM association with PEI was a topic of considerable ambiguity, with reported prevalence of PEI varying between 29% and 64% in CP patients with diabetes 23,30 . However, there is an emerging body of evidence that PEI represents one the risk factors for PPDM, 30,34 which highlights the need to further understand the mechanistic underpinnings of the endocrine‐exocrine interactions of the pancreas 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect when diagnosing a pancreatitis patient with new-onset diabetes is a high suspicion of occult malignancy. Chronic pancreatitis is a risk factor for both diabetes and pancreatic cancer, and new-onset diabetes can be an earlier marker of pancreatic cancer [ 5 , 35 , 36 ]. Thin subjects who are >50 years old at the time of diabetes diagnosis, with sudden weight loss and severe hyperglycaemia are at the highest risk of developing pancreatic cancer, and clinicians should have a low threshold for abdominal imagining (CT or MRI/MRCP) in these patients [ 5 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Bei chronischer Pankreatitis beträgt die Diabetesprävalenz nach 5 Jahren 33 %, bei ca. der Hälfte der Patienten mit Insulinabhängigkeit [ 15 , 18 , 57 ]. Umgekehrt prädisponiert das Vorbestehen eines Diabetes mellitus für die Entwicklung einer akuten Pankreatitis und einen schweren Verlauf [ 49 , 54 ].…”
Section: Klinische Relevanz Der Nebendiagnose Diabetes Mellitusunclassified